Problem Relasi Dialektis Dan Toleransi Antar Umat Beragama Dalam Masyarakat Multikultural - Faizal, Liky; Wakhid, Ali Abdul; Qohar, Abd (Universitas Islam Negeri Raden Intan Lampung, 2023)
In a multicultural society, conflict and integration are a dialectical pair. Tension, or in sociological technical language is conflict, is a unity with pluralism (pluralism). The social relations that exist between interfaith people never run in a fixed state, but take place in a situation that continues to change from one time to another. This is in line with the human tendency itself which is always changing. According to the perspective of social exchange theory, the tendency of interfaith social relations that tend to keep changing is a normal phenomenon in the lives of religious people which always fluctuates, because religious people always touch, hang out and socially interact with each other. Through interaction between religious communities, each other gives meaning to the attitudes and social behavior of religious people in a dialectical manner. Religious people actively and creatively interact and respond to each other. Therefore, the social environment which consists of verbal symbols, nonverbal symbols and the physical environment greatly influences how religious people interact cross-religiously. Fluctuations in interaction between religious believers occur because they are influenced by the social environment. When the social environment is positive, the interaction between religious people takes place effectively, peacefully, tolerantly and openly. On the other hand, when the social environment is not conducive, inter-religious relations are jammed.